Pelatihan Baca Tulis Al-Qur’an Pada Peserta Didik di SMA Negeri 1 Sinjai - Suriyati, Suriyati; Musdalifah, Musdalifah; Mustamir, Mustamir; Kahar, Kahar; Nur, Taufiq (PENDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This training aims to find out the extent to which SMA 1 Sinjai students are able to recite the Koran and write mushaf equally through the law of reading. The method used in this training is the Iqra method, because this training is carried out by asking students to learn to write hijaiyah letters and testing students' ability to read the Al-Qur'an. The benefit obtained from this training is that we can understand that BTA training is important because we know that the Koran is the main guideline of Islam and a guide for all mankind. This creative and innovative form of learning is prepared through training in reading and writing the Koran. The training is not just about reciting the Koran, but also writing hijaiyah letters with different pronunciations of the letters. Zikr is a form that can help students read the Al-Qur'an correctly according to their memorization. At SMA 1 Sinjai, it is one of the targets for organizing training in reading and writing the Al-Quran. This training is carried out so that students can love and study the Koran from now on. The results of this activity were carried out with the aim of producing a broad understanding of the development of learning to read and write the Koran. which was developed at SMA 1 Sinjai to increase students' interest in learning the Koran. With this training, it is also hoped that it can provide in-depth knowledge to improve learning to read and write the Koran in Islamic education.